(untitled) (Journal of Hama University, 2024)
The study was conducted during 2021-2022 growing seasons at AL- Suwaydah village, West AL-Raqqa governorate to study the aim of the research was to study the effect of organic fertilization and the level of irrigation on some physical properties and the productivity of maize ( Zea maize L.) in sandy soil. The experiment was designed in a randomized complete block, with split plot method. Where the split plots occupied two irrigation treatments of 70% and 100% of the field capacity, and the other treatments were randomly distributed within the two irrigation treatments (compost of Cities trash, sheep manure, mineral fertilizer and control).The study showed that the organic fertilizer treatments were significantly superior to the rest of the treatments in the values of total porosity and total productivity, where the waste compost treatment was the best in raising the productivity of the corn crop to (6.855) ton/ ha, with an increase of 35% compared to the control, at the irrigation level of 70%. The results also showed the possibility of obtaining similar results from the total productivity with the possibility of reducing the consumed amount of irrigation water by 30% compared with control. The organic additions led to significant decrease values of real and bulk densities by 28-29%, which reflected positively on the soil structure, the stability of the soil aggregation, and the increase in the soil’s ability to retain water. On the other side, the organic additions reduced the total porosity values of the sandy soil reached to 30%.